Poly (lactic acid)-Based triboelectric nanogenerators: Pathways toward sustainable energy harvesting - Kariyappa Gowda Guddenahalli Shivanna; Vishnu Kadabahalli Thammannagowda; Smitha Ankanahalli Shankaregowda; Stephane Panier; Prashantha Kalappa (Hybrid Advances)
The increasing integration of green energy across various sectors aims to promote sustainable development and environmental protection. With advancements in microfabrication and microelectronics, there is a growing demand for microscale energy sources to power modern technologies, including implantable devices and portable electronics. Current portable devices primarily depend on conventional chemical batteries, leading to environmental contamination and resource depletion. In response, triboelectric nanogenerators (TENGs) have emerged as promising solutions for energy harvesting, utilizing the principles of electrostatic induction and triboelectrification to convert mechanical energy into electrical energy. This review focuses on developing biodegradable TENGs, particularly polylactic acid (PLA) and other biopolymers, which offer significant advantages due to their biodegradability, mechanical strength, and processability. By enhancing the output performance of TENGs through innovative design and the incorporation of nanomaterials, this study explores the potential of fully biodegradable devices fabricated using environmentally friendly methods, such as 3D printing and compression molding process. This approach not only addresses the challenges associated with electronic waste but also contributes to the advancement of sustainable energy solutions in the field of bioelectronics.